2017
DOI: 10.1002/ange.201711824
|View full text |Cite
|
Sign up to set email alerts
|

Actinide–Pnictide (An−Pn) Bonds Spanning Non‐Metal, Metalloid, and Metal Combinations (An=U, Th; Pn=P, As, Sb, Bi)

Abstract: 3 ,A n = U, Pn = P, As,S b, Bi;A n = Th, Pn = P, As;T ren TIPS = N(CH 2 CH 2 NSiPr i 3 ) 3 ,A n= U, Pn = P, As,S b; An = Th, Pn = P, As,S b].T he UÀSb and ThÀSb moieties are unprecedented examples of any kind of AnÀSb molecular bond, and the UÀBi bond is the first two-centre-two-electron (2c-2e) one.The ThÀ Bi combination was too unstable to isolate,u nderscoring the fragility of these linkages.H owever,t he U À Bi complex is the heaviest 2c-2e pairing of two elements involving an actinide on am acroscopic sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…[9] TheU 1 ÀO1, U1ÀP1, U2À P1 bond distances are 2.226(8), 2.845(4), and 2.866(3) , respectively,a nd are unexceptional. TheU 1 À C1 distance of 2.478 (15) ,i ss horter than distances of 2.576(12)-2.598 (11) [12] which together with the acute P-C-O angle suggests the C-atom in 3 possess some carbene character when highly reduced by backbonding, analogously to some reduced CO 2 and CS 2 complexes. [15] TheU À N amide (av.2.324(11) )and U À N amine (av.2.790(9) ) distances are averaged by the disorder,and towards the high end of such distances.T his most likely reflects the overall anionic charge state of the diuranium component of 3,b ut may also reflect the presence of uranium(III) character since the anion portion of 3 can be formulated as a" high spin" diuranium(III)/PCO-monoanion or am ixed-valence diuranium(III/IV)/PCO-highly-reduced "low spin" form.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[9] TheU 1 ÀO1, U1ÀP1, U2À P1 bond distances are 2.226(8), 2.845(4), and 2.866(3) , respectively,a nd are unexceptional. TheU 1 À C1 distance of 2.478 (15) ,i ss horter than distances of 2.576(12)-2.598 (11) [12] which together with the acute P-C-O angle suggests the C-atom in 3 possess some carbene character when highly reduced by backbonding, analogously to some reduced CO 2 and CS 2 complexes. [15] TheU À N amide (av.2.324(11) )and U À N amine (av.2.790(9) ) distances are averaged by the disorder,and towards the high end of such distances.T his most likely reflects the overall anionic charge state of the diuranium component of 3,b ut may also reflect the presence of uranium(III) character since the anion portion of 3 can be formulated as a" high spin" diuranium(III)/PCO-monoanion or am ixed-valence diuranium(III/IV)/PCO-highly-reduced "low spin" form.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In recent years,wehave been investigating the coordination chemistry of triamidoamine complexes of uranium and thorium, [10] and in particular complexes of the type [U-(Tren TIPS )X] n or [{U(Tren TIPS )} 2 (m-X)] n [Tren TIPS = N(CH 2 CH 2 NSiPr i 3 ) 3 ;X = formally charged ligand; n = 0o r À1].T he list of main group X-ligands is extensive and growing, and includes:-NH 2 , = NH, N, -PH 2 , = PH, m-P(H), m-P, m-cyclo-P 5 ,-AsH 2 , = AsH, m-As(H), m-As, AsK 2 , m-h 2 :h 2 -As 2 , m-h 2 :h 2 As 2 H 2 , m-h 3 :h 3 As 3 ,-E(SiMe 3 ) 2 (E = P, As,Sb), = O, m-S, m-h 2 :h 2 S 2 , m-Se,a nd m-Te. [11] It is clear, therefore,t hat uranium-Tren TIPS in mono-or bi-metallic formulations is highly effective at trapping otherwise elusive,r eactive main group fragments,and this can involve unusual, highly reduced formal charge states that are stabilised by U-X p-o rdbonding. [11g,i] We therefore sought to determine if ah ighly reduced form of the OCP À anion could be prepared and trapped in auranium-Tren TIPS coordination environment.…”
mentioning
confidence: 99%
“…1 Transition metal (TM) based hetero-and homo-bimetallic complexes historically dominate this area of research, 2 but more recently examples of s-and p-block metal-metal complexes have been reported, [2][3][4] along with a recent surge in f-block examples. [5][6][7][8] In particular for the actinide (An) elements uranium and thorium, structurally characterized examples are now known of unsupported or supported metal-metal bonds for U-Al, 9 , U-Ga, 10,11 U-Sn, 12,13 , U-As, 14,15 U-Sb, 14 , U-Bi, 14 U-Mo, 16 U-Re, [17][18][19] U-Fe, [20][21][22] U-Ru, 23 U-Co, [24][25][26] U-Rh, 28 U-Ni, 29 U-Pd, 29 U-Pt, 29 U-Ag, 30 Th-Sb, 14 Th-As, 14,31,32 Th-Te, 33 Th-Fe, 34 Th-Ru, 35 Th-Co, 26 Th-Ni, 36 Th-Pt, 37 Th-Cu. 38 We and others have recently reported examples of hetero-bimetallic An-TM linkages supported by bridging phoshpino-amide linkages;…”
Section: Introductionmentioning
confidence: 99%
“…This aligns nicely with the recently reported (Tren R )Th[P(SiMe3)2], Tren = N(CH2CH2NR)3, R = DMBS = Si i Pr3, which displays a 31 P NMR signal at -100.09 ppm, and R = TIPS = SiMe2 t Bu, at -66.45 ppm. 195 As the substituent on phosphorus gets more donating, from mesityl to SiMe3 to H, then the shift is to lower frequency. For example, in comparing (C5Me5)2Th(Cl)(PMes2), 1, (C5Me5)2Th(Cl)[P(SiMe3)(Mes)], 7, and (C5Me5)2Th(Cl)[P(SiMe3)2], the 31 P NMR resonances move from +114.8 to +24.8 to -109.0 ppm, respectively, by changing from two to one to zero aryl groups on the phosphido phosphorus and from zero to one to two silyl groups.…”
Section: Experimental General Considerationsmentioning
confidence: 99%
“…This is because the coordination chemistry of the actinides is dominated by hard donor ligands, with the number of U(III) complexes with the heavier congeners of the chalcogen group being limited [90][91][153][154][155][156][157][158][159][160][161] , and no U(III) complexes have been reported with any element other than nitrogen in the pnictogen series. However, thorium(IV) 80,130,152,162 and uranium(IV) [163][164][165] complexes of phosphorus, arsenic, antimony 166 , and bismuth 166 are known, but also rare.…”
Section: Phosphido Complex Introductionmentioning
confidence: 99%